Horticultural education: present status and future prospects - Dutt, Som (Indian Horticulture, 2019)
As a part of Golden Jubilee Celebration, IIHR, Bengaluru, organised a â€œNational Conference on Horticultural Education: Present Status and Future Prospectsâ€ on 24 September 2016. This conference was inaugurated by Dr N.S. Rathore, Deputy Director-General (Education) ICAR, New Delhi. Dr R Venugopalan, Chairman, Post Graduate Education welcomed all the dignitaries and participants. Dr M.R. Dinesh, Professor and Director addressed the participants on this occasion and honoured the guests.